International Business - Luo, Yadong; Shenkar, O.; Chi, T. (Routledge., 2015)
Welcome to the companion website for International Business, 3rd edition by Oded Shenkar, Yadong Luo, and Tailan Chi. The third edition of International Business offers an action-focused, practical approach to the topic, helping students understand the global business environment and its repercussions for executives. The book provides thorough coverage of the field, delving into fundamental concepts and theory; the cultural, political, and economic environment; international business strategies; and even functional management areas. International Business combines broad and insightful coverage with practical application and global examples, providing students with a solid understanding of the field, and the tools to succeed within it.